1983
DOI: 10.1111/j.1365-2222.1983.tb02618.x
|View full text |Cite
|
Sign up to set email alerts
|

Allergy to inhaled egg material

Abstract: Summary The use of a spray system to coat meat rolls with egg solution resulted in the development of asthmatic type symptoms in eight of thirteen workers exposed to the spray. Symptoms were severe in five workers, less severe in two, and one worker experienced vague symptoms. Even though precipitins were present in nine of the workers there were no pyrexial episodes nor influenza‐like symptoms occurring some hours after inhaling the egg material to suggest extrinsic allergic alveolitis. All sera with precipit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

1986
1986
2002
2002

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 9 publications
3
18
0
Order By: Relevance
“…Milk, egg, nuts, and wheat are the most com mon allergens [2][3][4][5][6][7], Although potatoes are a very im portant vegetable, especially in Europe and North America, and, therefore, exposure is high, potatoes are rarely known to cause food allergy [8][9][10][11], In the present study sera were investigated from patients who showed allergic reactions to potatoes. By RAST using potato allergen disks, in all sera IgE specificities could be found, expressed in percent bindings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Milk, egg, nuts, and wheat are the most com mon allergens [2][3][4][5][6][7], Although potatoes are a very im portant vegetable, especially in Europe and North America, and, therefore, exposure is high, potatoes are rarely known to cause food allergy [8][9][10][11], In the present study sera were investigated from patients who showed allergic reactions to potatoes. By RAST using potato allergen disks, in all sera IgE specificities could be found, expressed in percent bindings.…”
Section: Discussionmentioning
confidence: 99%
“…The most important allergens in food allergies are egg, milk, nuts, and wheat [2][3][4][5][6][7], There are only few cases recorded in the literature of allergic reactions to potatoes. Pearson [8] described 29 female subjects with asthma who noted sneezing and/or wheezing while they were scraping unboiled potatoes.…”
Section: Introductionmentioning
confidence: 99%
“…The IgE-mediated reactions vary from ur ticaria and angioedema, flare-up of atopic dermatitis and gastrointestinal symptoms to asthma or even ana phylactic shock [2,8], These manifestations usually subside gradually throughout life and intolerance to egg or egg products is much less frequent in adults than in infancy. The ingestion of egg proteins seems to be the major route of sensitization, but occasional reports on allergy to inhaled egg material have been published [13,14,32], Food-allergic adult patients are often sensitized to pollens and such syndromes as concurrent IgE-medi ated allergy to tree pollens and fruits [15,16] or to Compositae pollens and vegetables (parsley family) [ 17,18] are now well recognized and thought to be due to antigen cross-reactivities. One of our patients, who started with asthma due to her budgerigar at the age of 42 and subsequently developed egg allergy, was ex clusively sensitized against bird feathers, egg-white and egg-yolk proteins, and made us aware that a simi lar cross-reactivity might exist for hen's eggs and other avian antigens.…”
Section: Introductionmentioning
confidence: 99%
“…One of our patients, who started with asthma due to her budgerigar at the age of 42 and subsequently developed egg allergy, was ex clusively sensitized against bird feathers, egg-white and egg-yolk proteins, and made us aware that a simi lar cross-reactivity might exist for hen's eggs and other avian antigens. Indeed IgG antibodies against egg-yolk proteins have been described in workers ex posed to egg spray [13,14,30] and recent research on extrinsic allergic alveolitis (pigeon's breeder lung) demonstrated cross-reactivity of precipitating anti bodies to bird antigens among several species [19,20] and with the water-soluble egg-yolk proteins known as 'livetins' [21][22][23]. However, only 1 patient with asthma was recently reported to have parrot-specific IgE antibodies cross-reacting with crude egg-yolk ex tracts [24], The present paper describes the results obtained in 59 atopic adults systematically skin tested with budgerigar and canary feathers, egg white, egg yolk and pure livetin extracts and all the common pneumo-allergens.…”
Section: Introductionmentioning
confidence: 99%
“…19 In this report, 8 of 13 bakery workers who sprayed a 251. mixture of egg white and yolk in water on meat rolls, developed respiratory symptoms . Only 5 of 8 were reported to complain of shortness of breath .…”
Section: B Mbdicalmentioning
confidence: 99%